2011
DOI: 10.1590/s1517-83822011000300036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sorghum straw hemicellulosic hydrolysate for biotechnological production of xylitol by Candida guilliermondii

Abstract: A preliminary study on xylitol production by Candida guilliermondii in sorghum straw hemicellulosic hydrolysate was performed. Hydrolysate had high xylose content and inhibitors concentrations did not exceed the commonly found values in other hemicellulosic hydrolysates. The highest xylitol yield (0.44 g/g) and productivity (0.19 g/Lh) were verified after 72 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 3 publications
(3 reference statements)
2
7
0
7
Order By: Relevance
“…Other xylitol fermentation research utilizing Candida guilliermondii cultivated on hemicellulosic hydrolysates from forage sorghum generated a xylitol yield around 0.35 g xylitol/g xylose consumed which also compares well with the yield calculated from Figure 4 [35]. Using C. guilliermondii on sorghum straw hydrolysate produced a yield of 0.44 g xylitol/g xylose consumed, which slightly outperforms the yield obtained here [36]. The results indicated that although the stillage media could support xylitol production, it might contain inhibitory compounds, which negatively affect the consumption rates of the two substrates, i.e., xylose and glycerol, especially when they accumulated to high levels due to concentration.…”
Section: Stillage Media With Detoxificationsupporting
confidence: 77%
“…Other xylitol fermentation research utilizing Candida guilliermondii cultivated on hemicellulosic hydrolysates from forage sorghum generated a xylitol yield around 0.35 g xylitol/g xylose consumed which also compares well with the yield calculated from Figure 4 [35]. Using C. guilliermondii on sorghum straw hydrolysate produced a yield of 0.44 g xylitol/g xylose consumed, which slightly outperforms the yield obtained here [36]. The results indicated that although the stillage media could support xylitol production, it might contain inhibitory compounds, which negatively affect the consumption rates of the two substrates, i.e., xylose and glycerol, especially when they accumulated to high levels due to concentration.…”
Section: Stillage Media With Detoxificationsupporting
confidence: 77%
“…The inhibitors concentrations (acetic acid 3.56 g L -1 , furfural 0.03 g L -1 , HMF 0.03 g L -1 and total phenols 0.89 g L -1 ) are within or under the range of values usually found in other sources of hemicellulosic hydrolysates, in general, 1-3.41 g L -1 of acetic acid, 0.04-0.26 g L -1 of furfural, 0.008-1.56 g L -1 of HMF and 2.12-2.23 g L -1 of total phenols (Mussatto & Roberto, 2004;Canilha et al, 2005;Marton et al, 2006;Villarreal et al, 2006;Sene et al, 2011).…”
Section: Methodssupporting
confidence: 75%
“…The quadratic trend can be related to an increased presence of inhibitor compounds, such as phenols (41,42) , that are released in higher extension as the severity of STE is greater. The total content of phenols compounds reported is 0.28 (43) , 1.35 (44) and 0.52 (45) g/100 g for COS, SOS and SUB, respectively. Another possibility is that as hemicellulose is solubilized, the proportion of crystalline cellulose increases, resulting in lower digestibility.…”
Section: Resultados Y Discusiónmentioning
confidence: 93%
“…La tendencia cuadrática puede estar relacionada a una mayor presencia de compuestos inhibidores, tales como compuestos fenólicos (41,42) que se incrementan según aumenta la severidad de la EXPV. El contenido total de compuestos fenólicos reportados son 0.28 (43) , 1.35 (44) y 0.52 (45) g/100 g para RM, RS y BZC. Otra posibilidad es que en el material tratado al solubilizarse la hemicelulosa, se incrementa la proporción de celulosa cristalina que se digiere más lentamente.…”
Section: Kinetics Of In Situ Digestionunclassified